Effects of Ni-decorated reduced graphene oxide nanosheets on the microstructural evolution and mechanical properties of Sn-3.0Ag-0.5Cu composite solders. (November 2022) - Zhang, Hehe; Xiao, Yuchen; Xu, Ziqi; Yang, Man; Zhang, Liping; Yin, Limeng; Chai, Sensen; Wang, Gang; Zhang, Long; Cai, Xinnan
Abstract: Introducing foreign reinforcements into solder joints has been demonstrated to be beneficial to promoting the soldering reliability. In this work, Ni-decorated reduced graphene oxide (Ni-RGO) nanosheets as foreign reinforcements were prepared through the in-situ thermal decomposition of Ni-glycolate@RGO complexes. xNi-RGO/SAC305 composite solders (x = 0, 0.01, 0.03, 0.05, 0.07, 0.1 wt%) were fabricated by the powder metallurgy method. The results showed that Ni nanoparticles were finely and evenly anchored on both sides of RGO nanosheets. The grain size in xNi-RGO/SAC305 composite solders was significantly refined, while the thickness of the interfacial intermetallic compounds (IMCs) decreased with increasing of Ni-RGO content. The average tensile strength of Cu/(Ni-RGO/SAC305)/Cu solder joints reached 43.0 MPa (18.1% higher than that of the plain SAC305 solder joints) when the amount of Ni-RGO addition reached 0.03 wt%, in which the crack initiation formed occurred in the soldering seam zone. The crack initiated in the micropores between the copper parent metal and composite solder when the content of Ni-RGO nanosheets was above 0.05 wt%, which may due to the agglomerating of submicron-sized Ni-RGO at the interface. These results suggest that traces of Ni-RGO nanosheets (0.03 wt%) can efficiently improve the interfacial bonding strength and solderability of the Cu/(Ni-RGO/SAC305)/Cu solder joint. Highlights: The RGO nanosheets were prepared through the in-situ thermal decomposition of Ni-glycolate@RGO complexes. The grains of xNi-RGO/SAC305 composite solders were significantly refined with the content of Ni-RGO up to 0.1 wt%. The tensile strength of the 0.03Ni-RGO/SAC305 solder joint was 18.1% higher than that of the plain SAC305 soldering.